Negative consequences of risks of digitalisation for consolidation of urban communities - Babintsev Valentin; Khripkov Kirill; Khripkova Dianna; Gaidukova Galina; Shapoval Zhanna (E3S Web of Conferences, 2022)
The purpose of the article is to assess the impact of digitalisation of the urban environment on the consolidation processes taking place in urban communities. The authors emphasize that digital technologies and services, social networks and messengers integrated into the urban space contribute to the development of alternative types of sociality, solidarity, subjectivity and consolidation of urban communities. The empirical basis of the article is the data of the sociological study “Social consolidation of urban communities: opportunities and limitations in the conditions of digitalisation of the urbanised environment”, conducted by a team of authors of the Belgorod State National Research University in 2022. As part of the study, N=1500 residents of the cities of Belgorod, Voronezh and Kursk regions were interviewed. To gain in-depth knowledge about the subject of the study, an expert survey was conducted (N=50), as well as a series of focus group interviews among 6 social groups: entrepreneurs, pensioners, municipal employees, youth, state employees and the unemployed. The total number of focus group participants is 57 people, the age range is 18-69 years, the gender composition is 34 women and 23 men. The theoretical analysis carried out, as well as the empirical data obtained, allowed us to identify some of the most significant risks of digitalisation that have negative consequences for social consolidation in an urbanised space: digital inequality, blurring of identity boundaries, multiplication of social statuses, technostress, increasing the possibility of controlling the private lives of citizens, loss of live communication, expansion of manipulative practices (dissemination of misinformation, unreliable rumors, post-truth or half-truth).